GAMBARAN SOAL-SOAL SEJARAH SISWA KELAS XI MAN SE-KABUPATEN PASAMAN BARAT - Lubis, Ripa Asyiah (Pendidikan Sejarah, 2014)
In teaching and learning procces on of the most influence components the succes of education is The Material learning material is subject that give by teacher to the student during teaching and learning procces in school. Science material in history is fact, concept and principle, otherwise cognitive aspects including memory, comperhension, application, analyze, sintetic and evaluation. Bot in fact science material of history tested in the matter of the dominant aspect of thinking those tested are comperhension and memory, supposed to sciencis material of history including fact, concept and principle with the other cognitive aspects. The aim of this study is to analysing the overview of history matters is sciencis material of histroy and material at thinking aspect that include in tested matter in semester (summative). The kind of this study is quantitative descritive by study location at MAN in West Pasaman. As for the source data of this study is obtaining data it gained from related school at semester form in 2012/2013 school year, through the study of documents and interview techniques. This data will be processed by classify with percentage. From the result of this study, we know that overview if history matters those tested at MAN in West Pasaman regency more tested science material of principle and fact while concept is not so balanced in tested matters, as well the overview of the material that tested by thinking aspect a lot more comperhension and memory, while the other thinking aspect has not been tested in matter. Based on result of this study can be concluded that many test material tested are fact and principle, it coused of teacherâs lack of understanding about science material who not fully understand the material facts, principle and concept and teacher only understand with principle and fact material only. But in aspect of thinking it tested such as memory, comperhension, application, analise sintetic and evaluation and the most tested is memory aspect/aspect of memory. It caused teacherâs lack of understanding about thinking aspect, so teacher just ask material from thinking and comperhensiont aspect.